2018
DOI: 10.1111/twec.12707
|View full text |Cite
|
Sign up to set email alerts
|

Firm heterogeneity and aggregate business services exports: Micro evidence from Belgium, France, Germany and Spain

Abstract: This paper uses detailed micro data on services exports at the firm–destination–service level to analyse the role of firm heterogeneity in shaping aggregate services exports in Belgium, France, Germany and Spain from 2003 to 2007. We decompose the level and the growth of aggregate services exports into different trade margins paying special attention to firm heterogeneity within countries. We find that the weak export growth of France is at least partly due to poor performance by small exporters. By contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 50 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previously, Baumgarten (2013), using the decomposition introduced by Juhn et al (1993), found a positive but moderate contribution of exporting companies to increasing wage inequality, predominantly within skill groups. 10 Lastly, the empirical evidence we have reviewed is largely restricted to the study of the manufacturing sector, and it ignores a set of well-documented facts, that is, the prominent role of trade in services (Ariu et al, 2019), the resilience of services to crises (Ariu, 2016) and the key role played by firm-level heterogeneity in services trade (Breinlich & Criscuolo, 2011;Loof, 2010). Services might possess unique attributes such as intangibility or inseparability, and this has some implications for trade.…”
Section: Literaturementioning
confidence: 99%
“…Previously, Baumgarten (2013), using the decomposition introduced by Juhn et al (1993), found a positive but moderate contribution of exporting companies to increasing wage inequality, predominantly within skill groups. 10 Lastly, the empirical evidence we have reviewed is largely restricted to the study of the manufacturing sector, and it ignores a set of well-documented facts, that is, the prominent role of trade in services (Ariu et al, 2019), the resilience of services to crises (Ariu, 2016) and the key role played by firm-level heterogeneity in services trade (Breinlich & Criscuolo, 2011;Loof, 2010). Services might possess unique attributes such as intangibility or inseparability, and this has some implications for trade.…”
Section: Literaturementioning
confidence: 99%